The Contextualization of Islamic Law Paradigms in the Pandemic Time Covid-19 as the Word of Religious Moderation - Saputera, Abdur Rahman Adi (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2020)
This study aims to investigate and analyze the adaptive and contextualization values of Islamic law during the Covid-19 pandemic, in order to occupy a more dynamic concept of religious moderation from a paradigm or thought perspective, by applying a design in the form of research (Library Research) using various library sources as the source of research data, it also applied a descriptive-normative approach to describe the pandemic as a real phenomenon, and began from the building as the source of the primary and secondary data to support, to be further processed using Fatwa No. 14 of 2020 and the Principles of Fiqhiyyah as a knife of analysis through the Descriptive Analytic Method Content process. The conclusions are drawn by applying inductive and deductive thinking methods. The contextualization effort in question is a form of embodiment of the value of religious moderation in a textual dichotomy but essentially integrates the moderation paradigm that has been popular so far focused in the washatiyah study discourse or only in tolerance between fellow of religious communities. The reflection of the paradigm of Islamic law during the pandemic period is to produce an ijtihad that commonly configures and elaborates normative texts with a progressive interpretation mode, as well as mediating and harmonizing the interrelation and domination of texts against existing realities, so that they actually produce an actual understanding as well as reflect the principles of Islamic law that is flexible, complete, and beneficial.